Self-Assembly of Materials and Their Applications - Rathnayake, Hemali; Pathiraja, Gayani; Sharmin, Eram (IntechOpen, 2023)
Self-Assembly of Materials and Their Applications provides foundational insight into self-assembly principles and supramolecular chemistry. It discusses coordination-driven self-assembly approaches, amphiphiles self-assembly, and nanoparticles self-assembly and their applications. Inspired by the nearly unlimited potential of nanomaterial-conjugated biomolecular structures, this book advances basic scientific knowledge of the synthetic and self-assembly methods that enable breakthrough capabilities for atomic-scale functional biomimetic objects, which make such bioinspired molecular platforms possible. The size-dependent optical, electrical, photochemical, and ionic properties of organized phospholipids with near-atomic-scale feature sizes are designed to provide high-density functional diversification, with nanometer-scale control for the development of biomolecular devices. For example, such a capability would drive bionano-heterogeneous sensor nodes, which are essential components of the Internet of Things. These structures also allow us to investigate the fundamental role of molecular confinement in biological sensing and corresponding signaling mechanisms.